Semiotyka dziwactwa - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The author assumes that the curiosity is a type of human expression. It can manifest in various languages and people’s behaviors, e.g.: verbal, mimic, gestural, costume and also by props, hairstyles, makeup etc. Regardless of differences between particular manifestations of the curiosity it is always semiotic. Freaks, eccentrics and weirdos disturb human community’s order and call into question established norms. They do that by their specific behaviors, appearances and individualism. They rectify, transform and change the social reality. The artistic curiosity not infrequently turn out to be the metaphor of an individual lifestyle (e.g. Witkacy, Dali). Freaks in the world of culture are not either savages or barbarians. They express themselves as well as they express their distance from the cultural system. In connection to this thesis, the author assumes that the curiosity is culture-producing.